Biochar-mediated remediation of nickel and copper improved nutrient availability and physiological performance of dill plants - Kazem Ghassemi-Golezani; Sedigheh Latifi; Salar Farhangi-Abriz (Scientific Reports)
Abstract The presence of heavy metals, such as copper and nickel, in the rhizosphere reduces the physiological efficiency and growth of plants. This study evaluated the effects of plum tree biochar levels (0, 15, 30, and 45 g kg-1 soil) with and without copper sulfate (200 mg kg-1 soil), nickel sulfate (400 mg kg-1 soil), and their combination on dill plants in a factorial experiment with a randomized complete block design in three replicates. The results indicated that the presence of copper and nickel in the soil had detrimental effects on the growth and physiological performance of dill. Specifically, copper stress alone reduced biomass by 31%, nickel stress by 27%, and their combined treatment by 37.7%. On the other hand, incorporating biochar into the soil decreased the uptake of heavy metals, oxidative stress, and the production of osmotic regulators in the plants, while enhanced nutrient uptake (N, K, Ca, Mg, Fe, and Zn), photosynthetic pigments, and plant biomass. Increasing biochar application rate in the soil did not have any additional beneficial effect on growth and physiological characteristics of plants. These results suggest that the low rate of biochar (15 g kg-1) from agricultural wastes is an appropriate soil amendment to remediate copper and nickel pollutants in the rhizosphere to enhance nutrient availability and plant performance. Future research could focus on the long-term efficacy of biochar under diverse field conditions, soil types, and plant species to optimize sustainable agricultural practices.